FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS (STUDI PADA PERUSAHAAN PERBANKAN) - Alfina Arum Rahmadhani; Suhendro Suhendro (Universitas Sanata Dharma, 2022)
The Purpose of this research was to examine the effect of leverage, Bank Size, Credit Risk and Capital Adequacy Ratio (CAR) on Profitability. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) in 2019-2020. This study uses a purposive sampling technique, namely banking sector companies listed on the Indonesia Stock Exchange (IDX) consecutively in 2019-2020, and banking companies whose profits. The data analysis method used in this research is multiple linear analysis. The rresults of this study indicate that leverage and Credit Risk have an effect on Profitability, while Bank Size and Capital Adequacy Ratio (CAR) have no effect on Profitability Keywords: Profitability, Leverage, Bank Size, Credit Risk, Capital Adequacy Ratio.